1991
DOI: 10.3346/jkms.1991.6.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A study on changes of coagulation inhibitors and fibrinolysis inhibitors in patients with liver cirrhosis and hepatoma

Abstract: The authors conducted an investigation focusing mainly on the activities of the inhibitory factors of the coagulation and fibrinolysis processes in 35 normal adults and 72 liver cirrhosis and/or hepatoma patients. The activities of antithrombin III, protein C, and alpha 2-plasmin inhibitor were reduced to less than 50% in patients with decreased hepatic synthetic function while lupus anticoagulant was detected in more than 50% of patients with decreased hepatic synthetic function. Hemostatic abnormalities in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 1 publication
1
8
0
1
Order By: Relevance
“…This would provide important information for developing a protocol for perioperative hemostasis management for recipients in this part of the world, which might be different from other protocols used in overseas centers. However, the observed incidence of 25.2% for increased lupus anticoagulant in our study is in line with the increased incidence of lupus anticoagulant between 18 and 61% reported by other authors [27,28,29,30,31] for patients with hepatitis C, cirrhosis, and carcinoma. Notably, the main transplant indication in our patient population was HCV infection in 82% (41/50), even combined with HCC in 43% (18/41).…”
Section: Discussionsupporting
confidence: 79%
“…This would provide important information for developing a protocol for perioperative hemostasis management for recipients in this part of the world, which might be different from other protocols used in overseas centers. However, the observed incidence of 25.2% for increased lupus anticoagulant in our study is in line with the increased incidence of lupus anticoagulant between 18 and 61% reported by other authors [27,28,29,30,31] for patients with hepatitis C, cirrhosis, and carcinoma. Notably, the main transplant indication in our patient population was HCV infection in 82% (41/50), even combined with HCC in 43% (18/41).…”
Section: Discussionsupporting
confidence: 79%
“…It is broadly accepted that both blood clotting tests such as one-stage prothrombin time and partial thromboplastin time as well as specific clot ting factor measurements have proved to be of additional value in the diagnosis and as sessment of liver diseases [8][9][10][11], It has been reported that AT III plasma level is a good index of liver function [12], Decreased activ ity of AT III and protein C in patients with decreased hepatic synthetic function has been reported [13], In the patients with liver cell damage resulting from chronic alcohol con sumption a low level of protein C was found. Among several parameters tested a decline in protein C level was the earliest detectable and the most pronounced disturbance in the coag ulation system accompanying hepatocellular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…A noncomprehensive list of these clinical associations includes carcinoma of the lung [6], kidney [7], breast [8], colon [8], liver [9], stomach [10], and ovary [11]. Many sporadic reports have also been published on hematological disorders that associate with aPL/APS.…”
Section: Clinical Associationsmentioning
confidence: 99%